Effect of Impeller Agitation on Preparation of Tetra-n-Butyl Ammonium Bromide Semiclathrate Hydrate Slurries - Shunsuke Hashimoto; Hiroyuki Ito; Kazunari Ohgaki; Yoshiro Inoue (International Journal of Chemical Engineering)
The slurries-containing tetra-n-butyl ammonium bromide (TBAB) solution and its semiclathrate hydrate have attracted a lot of interest as latent heat transport media. These hydrate slurries contain some microparticles of crystal, and the size and shape of these hydrate particles could affect the mobility of slurries. Hence, it is essential to investigate the efficient hydrate-slurry preparation methods and the effect of hydrate particles on the fluid property of slurries for the application to latent heat transport media. In the present study, the effect of agitation on particle size distribution and aggregation of particles was studied to prepare easily flowing TBAB hydrate slurries that were suitable for fluid transport. First of all, the effects of impeller rotational speed and impeller type on the particle size and frequency of aggregation were investigated. The results suggested that the particle size distribution and the frequency of particle aggregation are strongly affected by the intensity of shear rate and its uniformity, which was controllable with impeller type and its rotation speed.